2023
DOI: 10.1590/1678-4685-gmb-2022-0217
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing in maize: Toward improving complex traits in a global crop

Abstract: Recent advances in genome editing have enormously enhanced the effort to develop biotechnology crops for more sustainable food production. CRISPR/Cas, the most versatile genome-editing tool, has shown the potential to create genome modifications that range from gene knockout and gene expression pattern modulations to allele-specific changes in order to design superior genotypes harboring multiple improved agronomic traits. However, a frequent bottleneck is the delivery of CRISPR/Cas to crops that are less amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…For instance, researchers have successfully utilized viral delivery of CRISPR/Cas9 to create maize plants with stacked traits of disease resistance, insect tolerance, and improved drought tolerance. By editing specific genes associated with each trait, they generated ~ 786 ~ transgenic maize varieties capable of withstanding insect attacks, resisting common diseases, and maintaining productivity under limited water availability (Hernandes-Lopes et al, 2023) [48] Moreover, viral delivery of CRISPR/Cas9 has shown the potential to target multiple genes involved in different metabolic pathways. This capability has been exemplified in the development of biofortified crops with enhanced nutritional value.…”
Section: Potential To Target Multiple Traits Simultaneouslymentioning
confidence: 99%
“…For instance, researchers have successfully utilized viral delivery of CRISPR/Cas9 to create maize plants with stacked traits of disease resistance, insect tolerance, and improved drought tolerance. By editing specific genes associated with each trait, they generated ~ 786 ~ transgenic maize varieties capable of withstanding insect attacks, resisting common diseases, and maintaining productivity under limited water availability (Hernandes-Lopes et al, 2023) [48] Moreover, viral delivery of CRISPR/Cas9 has shown the potential to target multiple genes involved in different metabolic pathways. This capability has been exemplified in the development of biofortified crops with enhanced nutritional value.…”
Section: Potential To Target Multiple Traits Simultaneouslymentioning
confidence: 99%
“…CRISPR/Cas9-based targeted mutagenesis has been shown to be a promising tool for GE in maize, allowing manipulation of genes underlying agronomic traits, including complex traits controlled by multiple genes ( Hernandes-Lopes et al, 2023 ). However, bringing such approaches to a commercial scale is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation recalcitrance of most maize genotypes, from temperate and tropical origins, is the main bottleneck for applying biotechnological solutions to this crop. In addition, most GE studies in maize are limited to temperate genotypes suitable for Agrobacterium tumefaciens -mediated transformation, such as the public inbred line B104 ( Kausch et al, 2021 ; Yassitepe et al, 2021 ; Hernandes-Lopes et al, 2023 ). Therefore, the lack of genotypes both adapted to different agroecological zones and amenable to GE technologies is a significant limitation to maize improvement efforts in tropical and subtropical regions, which encompass developing countries most impacted by global climate change ( Anderson et al, 2020 and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation